Effectiveness of a heparinoid‐containing moisturiser to treat senile xerosis. (10th October 2014) - Hayama, Koremasa; Takano, Yusaku; Tamura, Jin; Tagami, Hachiro; Terui, Tadashi
Abstract: Background and Objectives: With the increasing elderly population in Japan, skin problems have become a greater concern. A heparinoid‐containing moisturiser is frequently used in Japan, but there is a lack of evidence for its efficacy in treating senile xerosis. To determine whether there is a correlation between age and the hydration state of the stratum corneum (SC) assessed by skin capacitance, and to evaluate the efficiency of a heparinoid‐containing moisturiser and a bed bath to treat senile xerosis. Methods: We recruited 73 individuals to assess the hydration state of the SC on their flexor forearm by measuring their skin capacitance. To evaluate the efficacy of a heparinoid‐containing moisturiser on senile xerosis, we recruited seven inpatients with an inactive daily life (IDL) who had senile xerosis. They were treated with the moisturiser in addition to a bed bath in two different protocols, and we measured the skin capacitance on their flexor forearms on days 0, 7 and 14. Results: There was a weak negative correlation (−0.3854, P < 0.01) between skin capacitance and age. Following the moisturiser treatments, the seven inpatients had increased hydration of both arms on days 7 and 14. The skin capacitance of the right forearm slightly decreased on day 14, even though it was significantly different from day 0 ( P < 0.05). Conclusions: These findings indicate that treatment with a heparinoid‐containing moisturiser together with a bed bath is an effective method for treating patients who have senile xerosis and IDL.